Enhancing Bali MSMEs’ Competitiveness through Digital Strategies, Product Innovation, and Local Wisdom - I Putu Putra Astawa; I Gusti Ayu Lia Yasmita; Ngurah Wisnu Murthi (LPPM Institut Bisnis dan Informatika Kesatuan, 2026)
This research is motivated by the challenges faced by MSMEs in Bali amid the increasingly competitive era of digitalization, as well as the need to preserve local cultural identity as a source of differentiation. The main objective of this study is to analyze the influence of digital marketing strategies, product innovation, and local wisdom values on the competitive advantage of MSMEs in Bali. This research employs an explanatory quantitative approach using Structural Equation Modeling–Partial Least Squares (SEM-PLS), involving MSME actors who actively utilize digital technology in their business activities. The findings reveal that local wisdom has the most significant influence on competitive advantage, followed by product innovation. Meanwhile, the digital marketing strategy shows a positive yet statistically insignificant influence at the 5% significance level. Collectively, these three variables explain 85% of the variance in competitive advantage. This study contributes to the development of a glocalization model, integrating digital technology with local wisdom as a competitive strategy. The results provide important implications for policymakers and MSME practitioners in formulating adaptive, innovative, and culturally rooted business strategies.